The Role of Social Media Engagement Mediation in The Influence of Social Media Marketing Activity on Purchase Decisions - Rahmaniyati, Anes Sintya; Roosdhani, Rifqy; Ali, Ali (Raudhah Publisher, 2024)
This study examines the role of social media engagement mediation on the influence of social media marketing activities on purchasing decisions at My Fodee Shop. The results of the study show that social media marketing activities have a positive and significant effect on purchase decisions. In addition, in the variable Social Media Marketing Activity, there is a stronger positive and significant influence on purchasing decisions through the mediation of Social Media Engagement.